Deletion of LRP5 in VLDLR Knockout Mice Inhibits Retinal Neovascularization - Xia, Chun-hong (Public Library of Science, 2013)
The development and maintenance of retinal vasculature require a precise balance between pro-angiogenic and anti-angiogenic factors. However, mechanisms underlying normal homeostasis of retinal vasculature and pathological changes of disrupted retinal vessel development are not fully understood. Recent studies of the low-density lipoprotein receptor-related protein 5 (LRP5) and the very low-density lipoprotein receptor (VLDLR) mutant mice indicate that LRP5 mediates a pro-angiogenic signal while VLDLR mediates an anti-angiogenic signal in retinal vasculature. Mice with a loss of LRP5 display underdeveloped intraretinal vasculature associated with endothelial cell (EC) clustering and failed EC migration into deep retinal layers. In contrast, VLDLR knockout mice show overgrown intraretinal vasculature and subretinal neovascularization. To understand the mechanisms for the opposite retinal vascular abnormalities between LRP5 and VLDLR mutant mice and to test how a loss of LRP5 perturbs subretinal neovascularization caused by a loss of VLDLR, we have generated and characterized the retinal vasculature in LRP5/VLDLR double knockout (DKO) mice. Our data show that DKO mice develop substantial EC clustering without subretinal neovascularization. The absence of subretinal neovascularization in DKO mice is associated with inhibited migration of ECs into the photoreceptor cell layer. In addition, the transcription level of Slc38a5, which encodes a Müller cell specific glutamine transporter, is significantly reduced in DKO mice, similar to previously reported changes in LRP5 single knockout mice. Thus, LRP5 signaling is a prerequisite for neovascularization in VLDLR knockout mice. LRP5 may be an effective target for inhibiting intraretinal neovascularization.